Mobilidade sazonal da população na cafeicultura: análise socioespacial do fluxo de trabalhadores para o município de Carmo do Rio Claro/MG - Haroldo Junior Martins Cardoso (2017)
Coffee production is an agricultural activity more expressive in the South mesoregion / Southeast of Minas Gerais, constituting the economic base of many municipalities. The disparities produced by the process of agricultural modernization and crystallization of the coffee agroindustrial complex reflected a demand for labor, especially in areas where mechanization of the harvest was not consolidated and family agriculture still prevails. Hitherto a mobility, therefore, it has been a recurring alternative to suppress this need. This fact, which exalts a relevance of the seasonal work, associated with the spatial mobility approach of populations in the productive dynamics of agriculture. Although there are a number of studies that deal with internal displacements in Brazil, it is not as important as migrations as a consolidated expression of spatial mobility, the work with the production of the seasonal seasonality of flows to work in the coffee harvest. Given this shortcoming, this work aims to analyze the volumes and as main characteristics of seasonal mobility flows for a coffee harvest in the municipality of Carmo do Rio Claro / MG. An analysis involves as macro and micro scales, which, respectively, correspond to structural (macroeconomic) and subjective (subjective level) aspects that are subject to population movements in space. At the macro level, basic data, referring to the economic and social conditions of the municipality of Carmo de Rio Claro, with the purpose of the document of production of coffee in the southern region of Minas Gerais and action of external labor. The average level of the processes involved in the process and investigate how the motivations, the engagements and the perspectives of these subjects in relation to the enterprise in mobility. The contemplation of the analysis, the number of primary data stacks, extracted from the application of the semistructured questionnaire in a sample of sixty seasonal workers, who worked temporarily in the district of Vilelândia, belonging to the municipality of Carmo do Rio Claro-MG, during the period of Coffee harvest (from May to August). The results indicate that the formation of the agroindustrial complex of coffee abruptly changed the regional productive structure. It is known that this process does not occur in a homogeneous way, especially not in the context of family farming that cultivates coffee on steep slopes, which makes mechanization even more difficult. At the same time as the complex increases productivity in coffee, it also makes production more costly, including the constant need to implement machinery and supplies. Most seasonal workers are young rural workers and family agribusinesses from the municipality of Santaluz / BA, whose introduction is a means of a complex social network involved in capturing and organizing the workforce. In general, these workers seek mobility in a form of work and income to guarantee family support, as well as to contemplate some personal goal.